Incidencia de los costos logísticos en la importación de productos perecibles amparadas bajo el régimen de desaduanamiento directo en el Ecuador - Aspiazu Alcívar, Marcelo Daniel (2013)
In Ecuador, with the implementation of Customs System (Ecuapass), the process of direct customs clearance underwent a significant change, it was supposed to allow to the foreign trade operators to perform all customs import operations with absolute agility and coordination between State Agencies in charge of controlling the entry of goods into the customs territory. It’s so that any company that wish to nationalize the perishables staples, in bulk and other products referred in the Art. 94 of the Regulation Organic Code of the production, trade and investment (COPCI) must present a previous request to the authority designated by the SENAE. The agency that regulates and controls the entire process is the Servicio Nacional de Aduanas del Ecuador (SENAE), who through the computer system, allowing to the foreign trade operators: perform all its operations, reduce the associated time to compliance of customs formalities, and accompanied of the predisposition of customs functionaries to consolidate the denominated process……